The Impact of Storyboard That Media on Students' Critical Thinking Skills in Social Sciences Subjects in Elementary Schools - Susilawati; Neng Ranti; Muhammad Hanif; Ita Rustiati Ridwan; Nenden Sundari (Jurnal Ilmiah Sekolah Dasar, 2024)
In the current era of digital technology development, free-access design platforms can be used in education as an alternative technology-based learning medium. Researchers found that in elementary schools, social studies learning still used conventional methods such as lectures and very rarely used instructional media, so students were bored while studying. Therefore, this study aimed to analyze the effect of using Storyboard That media on students' critical thinking skills on the material of the Proclamation of Independence. This study used the Storyboard That website along with 5 essay questions with a cognitive level of C4-C6 (analyze, evaluate, create). This research is a Quasi-Experimental with Non-equivalent Control Group Design. The number of samples consisted of class VI A totaling 22 students as the control class and class VI B totaling 22 students as the experimental class. Data analysis techniques consisted of prerequisite tests of normality and homogeneity tests and Independent Sample T-tests. The Independent Sample T-test data results on the pretest data were 0.539 > 0.05 and the post-test. (2-tailed) of 0.000 <0.05. So, it can be concluded that there were significant differences in students' critical thinking skills between the experimental group that used Storyboard That media and the control class that only used conventional lecturing methods. It is proven that Storyboard That encourages students to think critically through various visualization stimuli. This implementation allows teachers to use it as appropriate social studies learning media to improve elementary school students' critical thinking skills.